Nonlinear bending and vibration analyses of quadrilateral composite plates. (April 2017) - Kumar, Amit; Singha, M.K.; Tiwari, Vikrant
Abstract: Linear and nonlinear analyses of shear deformable thin and thick arbitrary straight-sided quadrilateral plates are reported here using smoothed finite element technique. The Reissner-Mindlin plates are discretized with quadrilateral background cells. Then membrane and bending stiffness matrices of background quadrilateral cells are evaluated using edge-based smoothed finite element method(ES-FEM). The shear stiffness matrix is calculated based on " smoothed shear strain approach " and the performance is compared with " edge-consistent four-node quadrilateral finite element ". The convergence, accuracy and sensitivity to mesh distortion of the present quadrilateral element is examined. Thereafter, the nonlinear bending and vibration analyses of trapezoidal and arbitrary straight-sided quadrilateral composite plates are presented for which only limited analytical results are available in the literature. Highlights: Smoothed finite element is employed for Reissner-Mindlin quadrilateral plates. The convergence, accuracy and distortion sensitivity of the present element is studied. Nonlinear bending and free vibration problems of quadrilateral plates are presented.